Penentuan Siklus Estrus Berdasarkan Gambaran Sitologi Vagina dan Profil Hormon pada Rusa Timor - Marlene Mesang Nalley, Wilmientje; Handarini, Ristika; Rizal, Muhammad; Iis Arifiantini, Raden; Laswardi Yusuf, Tuty; Purwantara, Bambang (Jurnal Veteriner; Vol 12, No 2 (2011))
Determination of estrous cycle especially the length of estrous is an important role in improvingthe fertility and reproductive performance of farm animals. This study was aimed to observe thelength of estrous cycle and estrous period based on cytologic and estrogen (E2) and progesterone (P4)hormone profiles. Samples of vaginal smears were collected daily and stained with Giemsa. Bloodsamples were collected every two days using jugular vein implant catheter. The hormone profileswere analized by radio immuno assay. All data were analyzed descriptively. Results of this studyshowed that there were four lowest points percentage of parabasal epithelial cells with the averageof 14.25%, while the superficial epithelial cells showed four highest points (85.75%). The intervalsbetween lowest point of parabasal epithelial cell and the highest point of superficial cells were at 20,18, and 16 with the average of 18 days. This phenomenon showed a cyclical processed with almostthe same length of time of the actual an estrous cycle pattern in timor deer. The range of E2 concentration was 7.06 to 18.14 pg/ml and P4 concentration was 2.58 to 7.48 ng/ml. The intervaltime between the peak of E2 was 17 days which represented the estrous cycle of timor deer. It isconcluded that analysis of estrous cycle in timor deer can be detected by vaginal cytological andhormone analysis profiles.
Keywords: Vaginal cytology, estrogen, progesterone, estrous cycle, timor deer